Delgadillo, Javier (coord.) (2015). Por una geografía humanista: Ángel Bassols Batalla - Hernández Cordero, Adrián (Documents d’Anàlisi Geogràfica, 2017)
Delgadillo, Javier (coord.) (2015) Por una geografía humanista: Ángel Bassols Batalla Ciudad de México: UNAM-Ariel, 400 p. ISBN 978-607-747-111-0